Brief Report: Switching to Tenofovir Alafenamide, Coformulated With Elvitegravir, Cobicistat, and Emtricitabine, in HIV-Infected Adults With Renal Impairment. (1st February 2017) - Post, Frank A.; Tebas, Pablo; Clarke, Amanda; Cotte, Laurent; Short, William R.; Abram, Michael E.; Jiang, Shuping; Cheng, Andrew; Das, Moupali; Fordyce, Marshall W.
Abstract : Abstract: Tenofovir disoproxil fumarate is associated with renal and bone toxicity. In a single-arm, open-label study of 242 virologically suppressed, HIV-infected participants with creatinine clearance 30–69 mL/min who switched to elvitegravir/cobicistat/emtricitabine/tenofovir alafenamide, participants had stable creatinine clearance, significant and durable improvements in proteinuria, albuminuria, and tubular proteinuria ( P < 0.001), and significant increases in hip and spine bone mineral density through 96 weeks ( P < 0.001). Eighty-eight percent maintained HIV-1 RNA <50 c/mL at week 96. These longer-term results support the use of elvitegravir/cobicistat/emtricitabine/tenofovir alafenamide in HIV-infected individuals with mild-moderately impaired renal function.